A study on habitat adaptation of Chamaecladon Supergroup (Araceae) in eastern part of Kelantan, Malaysia - Mohammad Razak Ramlee (2012)
Shading and water depth significantly influenced the growth, biomass allocation, growth pattern, maturity and photosynthetic rate. The habitat adaptation of both species have influence it growth rate and maturity. Growth pattern for both species (Homalomena humilis and Homalomena grifithii) is very special that allowed them to survive in the harsh condition. Both species do not tolerance with the human disturbance. Human disturbance will cause this species to extinct. Normally, the habitats for both species are far from the human settlement and activity. Even though the sample site was the recreation area for the human, but the locations are isolated.Both species were similar in light density, human tolerance, and distance from water. The population seems to be in good condition due to its small size and way of survival, supported by many numbers of juveniles for population maintenance. Future study should focus on monitoring the population and estimating the population growth rate to adress the best management system of the species.